KEEFEKTIFAN MULTIMEDIA INTERAKTIF BERBASIS ETNOMATEMATIKA TERHADAP HASIL BELAJAR SISWA MATERI CIRI-CIRI BANGUN DATAR DI KELAS IV SEKOLAH DASAR - Sofia Indra Kusumawati; Sutrisno Sahari; Nursalim Nursalim (STKIP Pesisir Selatan, 2026)
The purpose of this research and development is to determine the validity and effectiveness of the development of interactive multimedia based on ethnomathematics material on the characteristics of flat shapes for fourth grade elementary school students. This research and development uses the ADDIE model which consists of the stages (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The subjects of this research were teachers and 27 fourth grade students of SDN Mrican 2. The data analysis techniques used were qualitative and quantitative descriptive analysis. Data collection techniques used observation, interviews, questionnaires, and tests. The results of this research show that. (1) The results of the material expert validity test were 94% with very valid criteria and media experts 78% with valid criteria. (2)The results of the limited test student effectiveness test obtained an average of 84.2% and the broad test student effectiveness test obtained an average of 83.5%. Both effectiveness assessments obtained a very effective category. It can be concluded that the Ethnomathematics-Based Interactive Multimedia on the Characteristics of Flat Shapes for Grade IV Elementary School Students is stated to be very effective for use in learning the material on the characteristics of flat shapes in grade IV SDN Mrican 2.